Environmental Attitude Generasi Z dan Pengaruhnya terhadap Minat Beli Green Product - Tania Adialita; Miryam Ariadne Sigarlaki; Sarah Febrina Yolanda (Universitas Batanghari, 2022)
Economic growth and patterns of consumer behavior that are moving very fast throughout the world are the main causes of environmental damage that have an impact on the growth and development of green consumerism, namely consumers who are starting to realize the presence of environmental aspects in their consumption patterns and want products that have a not bad impact on the environment. environment. This growing awareness of environmental issues or environmental awareness encourages consumers to have environmental concerns/attitudes which in turn changes consumer buying behavior towards green products. According to the World Wild Fund (WWF), in 2017 as many as 63% of consumers in Indonesia were willing to buy environmentally friendly products even at higher prices. However, the level of brand advocacy ratio and purchase action ratio of several products that are included in the green product category has not yet occupied the first position. This condition causes researchers to be interested in examining the condition of buying interest in green products in Indonesia, especially those influenced by environmental awareness and environmental attitude. The results of the study show that environmental awareness will have a positive impact on environmental attitudes, and environmental attitudes will affect buying interest in green products, then environmental awareness will have a positive effect on buying interest in green products through environmental attitudes. This is intended in order to provide information to green product business actors about the environmental attitude of consumers so that the established marketing strategy is able to form a positive attitude and ultimately be able to encourage consumers to purchase green products in the future. The method used in this research is descriptive – associative by using survey techniques in collecting related data. The questionnaire instrument will be tested for validity and reliability and the survey data will be analyzed using multiple regression and tested for significance with the t-test and Sobel test using SPSS Version 24. Data collection was carried out by distributing online surveys and obtaining a sample of 257 respondents from various cities in West Java.